Cover Image, Volume 42, Issue 7. Issue 7 (6th July 2022) - Chen, Xueman; Song, Erwei
Abstract : The cover image is based on the Review Article The Theory of Tumor Ecosystem by Xueman Chen et al., https://doi.org/10.1002/cac2.12316 .